2005
DOI: 10.1002/ijc.21409
|View full text |Cite
|
Sign up to set email alerts
|

Loss of intercellular adhesion activates a transition from low‐ to high‐grade human squamous cell carcinoma

Abstract: The relationship between loss of intercellular adhesion and the biologic properties of human squamous cell carcinoma is not well understood. We investigated how abrogation of E-cadherin-mediated adhesion influenced the behavior and phenotype of squamous cell carcinoma in 3D human tissues. Cell-cell adhesion was disrupted in early-stage epithelial tumor cells (HaCaT-II-4) through expression of a dominant-negative form of E-cadherin (H-2K dEcad). Three-dimensional human tissue constructs harboring either H-2K d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…Loss of E-cadherin has been correlated in clinical studies with various pathologic and clinical features, such as tumor dedifferentiation, infiltrative growth, and a poorer patient prognosis (37,38). In addition, UVR, a potent skin cancer inducer, has been shown to down-regulate E-cadherin expression in human tissue skin constructs in vitro; similar results have also been shown in human malignant skin lesions, suggesting that E-cadherin down-regulation plays a critical role in SCC progression (7)(8)(9).…”
Section: Cancer Researchsupporting
confidence: 53%
See 1 more Smart Citation
“…Loss of E-cadherin has been correlated in clinical studies with various pathologic and clinical features, such as tumor dedifferentiation, infiltrative growth, and a poorer patient prognosis (37,38). In addition, UVR, a potent skin cancer inducer, has been shown to down-regulate E-cadherin expression in human tissue skin constructs in vitro; similar results have also been shown in human malignant skin lesions, suggesting that E-cadherin down-regulation plays a critical role in SCC progression (7)(8)(9).…”
Section: Cancer Researchsupporting
confidence: 53%
“…Moreover, several groups have shown that defective E-cadherin function can render noninvasive cells invasive, whereas reestablishing functional E-cadherin complexes in tumorigenic cell lines reverts an invasive mesenchymal phenotype to a benign epithelial phenotype (4)(5)(6). In skin, in vitro work and studies using human malignant skin lesions suggest that decreased E-cadherin function plays a critical role in SCC progression (7)(8)(9)(10). However, exposure to chronic UV irradiation (UVR) remains the largest risk factor associated with the development of SCCs, and these prior studies did not determine the mechanism(s) by which E-cadherin expression is temporally regulated by acute or chronic doses of UVR in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…However, in early-stage tumor cells such as II-4, it is thought that mutation of the Ha-Ras gene may be more directly related to growth-regulatory pathways (Delhedde, 1999) rather than altering cell adhesion. As recently shown, E-cadherin-deficient-II-4 cells do not show all features of EMT (Margulis et al, 2005a), suggesting that the combinatorial effect of Ha-Ras activation, p53 loss and Ecadherin suppression are insufficient to fully induce EMT in these early-stage tumor cells.…”
Section: Discussionmentioning
confidence: 80%
“…Epidermal reconstructs were established in vitro with either control II-4 cells expressing pBabe or H-2k d -EcadC25 or with II-4 cells expressing a dominant-interfering E-cadherin (H2k d -Ecad). The H-2k d -Ecad transgene has previously been described to interfere with E-cadherin function in normal keratinocytes (Zhu and Watt, 1996) and II-4 cells (Margulis et al 2005a). This occurs as overexpression of this fusion protein leads to destabilization of endogenous E-cadherin-␤-catenin complexes upon the cytoplasmic sequestration of ␤-catenin by the dominant-interfering transgene and to loss of E-cadherinmediated intercellular adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Previous studies showed that decreased immunoreactivity of E-cadherin statistically correlated with the presence of lymph node metastases in esophageal squamous cell carcinoma, and loss of intercellular adhesion activates a transition from low-to high-grade squamous cell carcinoma, thus indicating an important role for E-cadherin as a prognostic marker in the progression of tumors. 24,25 Increased expression of the 80 kDa fragment of E-cadherin in metastatic prostate cancer in association with increased levels of several metalloproteinases, which are believed to be responsible for cleavage of short E-cadherin fragment from the full-length Ecadherin, are suggested to induce tumor progression in this tumor. 26 Metalloproteinases differentially expressed by tumor and stromal cells are finely regulated by interaction with distinct cellular and extracellular components of the tumor environment.…”
Section: Discussionmentioning
confidence: 99%